The magnitude of the injury pattern in femicides by stabbing in Colombian women (2017)
Introduction: Assessing the severity of the injuries suffered by victims may contribute to prevent femicide more effectively.Objective: To establish whether the amount of wounds recorded in femicides by stabbing vary according to the age of the victim and the victim-offender relationship.Materials and methods: Cases of Colombian women who were stabbed to death between 2011 and 2013 (n=331; age: 14-91 years) were included in the study. They were classified according to age ranges and the type of relationship with the offender. Descriptive analyses were conducted. Two one-way ANOVAs and a factorial ANOVA were performed to assess the differences in the mean number of the stab wounds received by the victim, and to determine the effects of interaction among the established categories.Results: The pattern of injury severity was higher in women aged 22 to 40 years than in those aged 41 to 55 years, and in women attacked by their intimate partners than in those attacked by strangers and acquaintances. Age ranges and types of relationship had an interaction effect on the dimension of the sustained wound.Conclusion: The age of the victims and the types of relationship they had with the offender are variables that should be considered to propose preventive policies on femicide since both are correlated to violent acts with greater injury patterns.